MENTAL DISABILITIES IN JOE PENHALL’S BLUE/ORANGE AND SARAH KANE’S 4:48 PSYCHOSIS - Mutashar, Hussein Zaboon (International Journal of Advance Research in Education & Literature (ISSN 2208-2441), 2022)
The focus of this research is on how mental disability is portrayed in drama to sway the audience's perceptions. Blue/Orange by Joe Penhall and 4:48 Psychosis by Sarah Kane will be examined in this research. The researcher is attempting to describe the many methods in which the disabled characters' understanding and empathy are sought determining how far the audience can sympathize with characters that have a profoundly distorted understanding of their own lives. Studying Penhall's work, researchers found that he portrays a crippled figure as a victim of oppression, shifting the emphasis away from depicting a disturbed mind. Studying Kane's work, the researchers found that it elicits pity for her characters and elicits intense emotional disturbance in the audience, but that it may be difficult for spectators to put themselves in the position of characters about whom they have little knowledge of their thoughts and emotions.